DOES THE USE OF STRATEGIC MANAGEMENT ACCOUNTING TECHNIQUES CREATES AND SUSTAINS COMPETITIVE ADVANTAGE? SOME EMPIRICAL EVIDENCE - OYEWO, Babajide; AJIBOLADE, Solabomi (Annals of Spiru Haret University. Economic Series, 2019)
This study examined the extent to which the usage of strategic management accounting (SMA) techniques such as customer accounting and competitor accounting can create and sustain competitive advantage, with a focus on the manufacturing sector in Nigeria. Data obtained from the annual reports of fifty-six (56) publicly-quoted companies covering a 10-year period (2008-2017) were analysed using descriptive statistics, cluster analysis, cross tabulation, Chi-square test of association, and discriminant analysis. Whereas the frequency of high-adopters of customer-based and competitor-focused techniques was less than those of low-adopters, the adoption rate of SMA was noted to be generally moderate. Further, the usage of SMA positively and significantly impact competitive advantage. The observation that intense users of SMA were able to consistently outperform competitors at both the industry- and sector- level in the long-term supports the conclusion that to a large extent, SMA usage can both create and sustain competitive advantage. Seeing that it is not the mere adoption of SMA that sustains competitive advantage but its intense usage, organisations seeking strategies to improve their competitiveness may consider the rigorous application of SMA.